Tafsir Pemikiran Muhammad Syahrur tentang Waris dan Kontribusinya Bagi Perkembangan Hukum Kewarisan di Indonesia (Studi Analisis Kompilasi Hukum Islam) - Sedayu, Rahmat Agung; Thahir, A. Halil; Mushlihin, Imam Annas; Tohari, Ilham (Institut Agama Islam Negeri (IAIN) Kediri, 2023)
In Muhammad Syahrur's view, waris is hududullahh which means that the maximum limit for a son is two daughters, and the minimum limit for a daughter is one boy. This research is qualitative research with the type of research library research which aims to reveal how Muhammad Syahrur's thoughts about inheritance with an analysis knife Compilation of Islamic Law. The data analysis process uses content analysis techniques, which are research techniques by looking for regular shapes, structures, and patterns in the text and making conclusions based on the regularities found. The results of this study: 1) Muhammad Syahrur rereads the inheritance verse which is hududullahh. If the heirs consist of one son and two daughters, then the share of the daughter may not be less than 25% and the share for the son may not be greater than 50%. 2) The contribution of Muhammad Syahrur's thoughts on inheritance to the development of inheritance law in Indonesia is by positioning the inheritance portion for women as al-Hadd al-'Adna (minimum limit). With this, Syahrur wants to say that women may or even have the right to get more shares than one man, provided that they do not exceed al-Hadd al'Ala for men. Thus women can get more shares than what has been determined by QS. An-Nisa verse 11 and article 176 KHI as long as it does not exceed the male share (½).